PEMANFAATAN CITA Pi-SAR2 UNTUK IDENTIFIKASI SEBARAN ENDAPAN PIROKLASTIK HASIL ERUPSI GUNUNGAPI GAMALAMA KOTA TERNATE - Suwarsono, Suwarsono; Yudhatama, Dipo; Trisakti, Bambang; Sambodo, Katmoko Ari (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2013)
This research aims to identify the distribution of pyroclastic deposits from the eruption volcano by using Pi-SAR2 imagery. The object of research is Gamalama Volcano, located in the city of Ternate in North Maluku Province. Research methods include radiometric calibration Pi-SAR2 to get the value of backscatter intensity sigma naught, calculation of statistical values (mean, standard of deviation and coefficient of correlation between bands) backscatter intensity of sigma naught among pyroclastic deposits and other surface objects, as well as the separation distribution of pyroclastic deposits using thresholding methods. This research concludes that the Pi-SAR2 imagery can be used to identify the distribution of volcanic pyroclastic deposits from the eruption. Concurrent use of polarization HH, VV and HV will give better results than using a single polarization HH and VV. This research suggests further research to be done by applying the method of verification is supported by the use of field data (ground check).